The Mediating Roles of GDP on the Relationship Between Income Inequality and Life Expectancy - Chia-Chang Chuang (Asian Academy of Management Journal, 2021)
This study examined the mediation effect of gross domestic product (GDP) on the relationship between life expectancy and income inequality based on data from 23 Organisation for Economic Co-operation and Development (OECD) countries for 2004 through 2014. To form a theoretical framework, Preston curve and Kuznets curve were employed. The study set up a mediation model with life expectancy as an outcome variable, GDP as a mediator variable, and three variables characterising income inequality as predictor variables: Gini index, income share held by highest 20%, and poverty headcount ratio at US1.90 a day. The study found that GDP clearly mediates the effects of the predictor variables on life expectancy, although the magnitudes of the effects vary. This study takes an important initial step in exploring the mediation effect of GDP on the relationship between life expectancy and income inequality.